ADVANTAGE OR TROUBLEMAKER: A PHENOMENOLOGICAL STUDY OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) OWNER RESPONSE TOWARD ACCOUNTING AND REPORTING - Fitri Purnamasari; Muhammad, Muhammad; Ferby Mutia Edwy; Inanda Shinta Anugrahani (Media Bina Ilmiah, 2025)
This study is motivated by the phenomenon that businesses classified as Micro, Small, and Medium Enterprises (MSMEs) often ignore one important aspect of business, namely financial reports. This study aims to capture the relationship between business owners' understanding of accounting and the preparation of financial reports. To interpret and re-understand the relationship between accounting understanding and accounting practices, phenomenology is used as a research methodology. The phenomenological method is considered capable of exploring the awareness and knowledge of business owners in terms of accounting and accounting practices. From this study, it was found that the level of accounting understanding has implications for the practice of preparing financial reports. In addition, other factors such as resources such as time, personnel, and costs also affect the practice of preparing financial reports in the context of this study.